2015
DOI: 10.1039/c5fo00729a
|View full text |Cite
|
Sign up to set email alerts
|

Novel fiber-rich lentil flours as snack-type functional foods: an extrusion cooking effect on bioactive compounds

Abstract: Novel snack-type functional foods based on extruded lentil flours could convey the related health benefit of their bioactive compounds, provide a gluten-free alternative to consumers, and potentially increase the consumption of pulses. Extrusion treatment promoted an increase in galactopinitol, ciceritol, raffinose, stachyose and total α-galactoside content, in most lentil flours. As α-galactosides may act as prebiotics, they could convey beneficial effects to human and monogastric animals. Conversely, extrusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
40
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 24 publications
(31 reference statements)
4
40
0
2
Order By: Relevance
“…The presence of anti-nutrients in legume seeds might not be an impediment, as proper processing methods can make them edible for a safe use [ 5 ]. Extrusion cooking technology is a high-temperature, short, and versatile food operation that converts agricultural raw materials into fully cooked and shelf-stable food products with enhanced nutritional attributes [ 6 ]. Legume extrusion cooking eliminates anti-nutritional factors and improves protein digestibility at a cost lower than other cooking systems [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The presence of anti-nutrients in legume seeds might not be an impediment, as proper processing methods can make them edible for a safe use [ 5 ]. Extrusion cooking technology is a high-temperature, short, and versatile food operation that converts agricultural raw materials into fully cooked and shelf-stable food products with enhanced nutritional attributes [ 6 ]. Legume extrusion cooking eliminates anti-nutritional factors and improves protein digestibility at a cost lower than other cooking systems [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Extrusion cooking technology is a high-temperature, short, and versatile food operation that converts agricultural raw materials into fully cooked and shelf-stable food products with enhanced nutritional attributes [ 6 ]. Legume extrusion cooking eliminates anti-nutritional factors and improves protein digestibility at a cost lower than other cooking systems [ 6 , 7 ]. Legumes could be included as protein sources in the extrusion process to formulate nutritionally enhanced functional food products [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Madhumitha and Prabhasankar () reported that there was an improvement in the nutritional value of pasta by adding black gram flour and mentioned that the processing of food material increases the value and shelf life of the product. Extrusion treatment of lentil flours has also been linked with increase in some bioactive components (Morales et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Extrusion treatment of lentil flours has also been linked with increase in some bioactive components (Morales et al, 2015).…”
Section: Introductionmentioning
confidence: 99%